Green Budgeting As an Instrument of Sustainable Fiscal Governance: A Systemic Literature Review - Yunita Yusuf, Yulia; Andi Faisal; Adriansyah (International Economic Conference of Business and Accounting, 2025)
Climate change has placed sustainability at the center of the global development agenda, yet the link between fiscal policy and environmental goals remains limited. This article offers a new perspective by positioning green budgeting not merely as a technical fiscal tool, but as an instrument of sustainable fiscal governance. Using a Systematic Literature Review (SLR) approach following the PRISMA protocol, as many as 40 relevant articles published between 2000 and 2024 were analyzed. The study’s findings indicate that the existing literature generally describes green budgeting in three ways: as a technical fiscal mechanism, a governance instrument, or a political tool. This article argues that green budgeting has transformative potential to bridge global sustainability commitments with national fiscal decision-making. By reframing it as a governance instrument, this article challenges the prevailing view, fills research gaps, and emphasizes the urgency of moving beyond symbolic adoption toward substantive sustainable fiscal governance.